2004
DOI: 10.1300/j027v23n01_01
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Intervention to Improve Heart Failure Outcomes in Community-Based Home Health Care

Abstract: This study examines the effects of a home health intervention designed to standardize nursing care, strengthen nurses' support for patient self-management and yield better CHF patient outcomes. Participants were 371 Medicare CHF patients served by 205 nurses randomized to intervention and control groups in a large urban home healthcare agency (HHA). The intervention consisted of an evidence-based nursing protocol, patient self-care guide, and training to improve nurses'teaching and support skills. Outcome meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 21 publications
1
20
0
2
Order By: Relevance
“…34,39 Some authors provided more detailed information than others regarding how implementation interventions were delivered, which made it challenging to determine what exactly was done. Facilitation activities varied in content, complexity, frequency, intensity, and duration (see Fig.…”
Section: Facilitation Process and Activitiesmentioning
confidence: 99%
“…34,39 Some authors provided more detailed information than others regarding how implementation interventions were delivered, which made it challenging to determine what exactly was done. Facilitation activities varied in content, complexity, frequency, intensity, and duration (see Fig.…”
Section: Facilitation Process and Activitiesmentioning
confidence: 99%
“…Strategies used in these initiatives have included passive dissemination of educational information to health care providers and patients, computerized order sets, automatically generated suggestions for care interventions, automated reminders attached to echocardiography results, as well as intensive education, direct feedback and care support from expert clinicians (161)(162)(163)(164)(165)(166)(167)(168)(169)(170)(171). Strategies that rely on passive dissemination of information to health care providers are, at best, modestly effective (162,167,168).…”
Section: What Care Improvement Mechanisms Should Be Considered?mentioning
confidence: 99%
“…Non significant trend towards more improvement with usual care. Generic QoL improved with usual care and worsened with intervention De Lusignan et al [157] To assess the effect of home telemonitoring Feldman et al [143] To assess the effect of a home health intervention designed to standardize nursing care, strengthen nurses' support for patient self-management and yield better CHF patient outcomes. 371 NS Evidence-based nursing protocol, patient self-care guide and training to improve nurses' teaching and support skills or control 13 MLHF No significant differences in QoL…”
Section: Surgical/procedural Trialsmentioning
confidence: 99%
“…Nine of the interventions reported no significant QoL effect [27,60,65,77,130,143,157,160,176]. Ojeda and colleagues [126] completed a 12-month follow-up of a study reporting beneficial effects of a discharge intervention and found that the benefits were not present at followup.…”
Section: Patient Care and Service Management Interventionsmentioning
confidence: 99%